(untitled) (United Journal of Interdisciplinary Studies, 2024)
This study explores the usage of translanguaging in English as a Foreign Language (EFL) classrooms, drawing insights from ELT instructors with over a decade of teaching experience and college students aged 17-20. The research investigates the advantages and disadvantages of translanguaging, its impact on student engagement, comprehension, and retention. Findings reveal that while translanguaging enhances cultural understanding, motivation, and competitiveness, challenges include L1 interference and potential confusion in communicative structures. Students’ perspectives highlight the positive impact of translanguaging on learning, emphasizing its role in facilitating deeper comprehension and memory retention. The study delves into the reliance on the first language (L1) and discussions among instructors advocate for supportive institutional policies to encourage translanguaging. The analysis underscores the need for a balanced approach, recognizing translanguaging as a valuable tool when strategically implemented.